2021
DOI: 10.1002/acm2.13390
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose for 320‐row dose‐modulated dynamic coronary CT angiography

Abstract: Objectives The area detector 320‐row CT scanner, which can cover the whole heart in one rotation, can aid in reducing radiation exposure during electrocardiography (ECG)‐gated coronary CT angiography (CCTA). Recently, researchers have proposed dose‐modulated dynamic CCTA with a 320‐row scanner for the detection of functional myocardial ischemia. In the present study, we compared and validated the radiation dose of this method with that of the standard CCTA method and the latest diagnostic reference levels (DRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It has recently been reported that dynamic CCTA scanning can estimate functional myocardial ischemia [35] and can also estimate myocardial blood flow via ammonia PET [1] . The scan protocol used in this study, which combines standard CCTA with low-dose dynamic imaging using a 320-row scanner, does not increase radiation exposure as compared to conventional CCTA [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that dynamic CCTA scanning can estimate functional myocardial ischemia [35] and can also estimate myocardial blood flow via ammonia PET [1] . The scan protocol used in this study, which combines standard CCTA with low-dose dynamic imaging using a 320-row scanner, does not increase radiation exposure as compared to conventional CCTA [23] .…”
Section: Discussionmentioning
confidence: 99%
“…One scan of the dynamic CCTA was performed as a boost scan for standard CCTA at the peak phase of the ascending aorta. The scan parameters were as follows: gantry rotation time, 0.275 s; detector collimation, 320 × 0.5 mm; tube voltage, 100 kV; tube current, 80 mA at the dynamic scan, and auto radiation exposure reducing control at the boost scan with a field of view of 200 mm [23] .…”
Section: Methodsmentioning
confidence: 99%
“…Ordinary CT scans take 1 to 10 s per slice, but recent CT scanners have many rows of detectors, some up as high as 320 rows, that can take multiple x-rays of the heart simultaneously ( 96 ). This type of technology is called multidetector computed tomography (MDCT), and MDCT is considered the new gold standard for preoperative planning ( 97 ).…”
Section: Cardiac Ctmentioning
confidence: 99%
“…Head CT requires high contrast resolution with low image noise. When helical CT is used, the pitch factor (PF) is set to <1.0 and the tube current is set to high, with a resulting radiation dose that is higher than that to chest, abdomen, and other imaging sites imaged with a lower PF 9–14 . When the PF is <1.0, some areas are irradiated twice, increasing the dose.…”
Section: Introductionmentioning
confidence: 99%
“…the pitch factor (PF) is set to <1.0 and the tube current is set to high, with a resulting radiation dose that is higher than that to chest, abdomen, and other imaging sites imaged with a lower PF. [9][10][11][12][13][14] When the PF is <1.0, some areas are irradiated twice, increasing the dose. The lens is often directly irradiated twice.…”
mentioning
confidence: 99%